Toxicological Assessment of Pseudospondias microcarpa (A. Rich.) Engl. Hydroethanolic Leaf Extract in Rats: Haematological, Biochemical, and Histopathological Studies - Donatus Wewura Adongo; Priscilla Kolibea Mante; Kennedy Kwami Edem Kukuia; Charles Kwaku Benneh; Robert Peter Biney; Eric Boakye-Gyasi; Nicholas Akinwale Titiloye; Eric Woode (The Scientific World Journal)
Pseudospondias microcarpa is used traditionally for treating various diseases. However, although parts of the plant are extensively used in African traditional medicine, no scientific study has been reported on its toxicity. Therefore, this study evaluated the acute and subacute toxicity studies of the ethanolic extract of P. microcarpa in rats. Male Sprague-Dawley rats (120–150 g) were treated orally with the extract (30, 100, 300, 1000, and 3000 mg kg−1) or distilled water (10 ml kg−1) for 2 weeks and observed daily for general appearance and signs of toxicity. In addition, blood was collected for both biochemical and haematological assays. Sections of tissues from liver, kidney, spleen, brain, and stomach were also used for histopathological examination. Administration of the extract for 14 consecutive days caused no deaths, with an LD50 above 3000 mg kg−1. Except for lymphocytes (%) that showed a significant decrease (F5,23=3.93, P=0.013), all other haematological parameters remained unaffected by the extract. The extract at 100 mg kg−1 showed a significant decrease in the levels of triglyceride and very-low-density lipoproteins (both at P<0.05). Weight change as well as histological evaluation of the organs indicated no toxicity. The study demonstrates that an ethanolic extract of P. microcarpa given orally to rats is safe.